Prevalence of asymptomatic heart failure in formerly pre‐eclamptic women: a cohort study. (January 2017) - Breetveld, N. M.; Ghossein‐Doha, C.; van Kuijk, S. M. J.; van Dijk, A. P.; van der Vlugt, M. J.; Heidema, W. M.; van Neer, J.; van Empel, V.; Brunner‐La Rocca, H.‐P.; Scholten, R. R.; Spaanderman, M. E. A.
ABSTRACT: Objectives: After pre‐eclampsia (PE), the prevalence of structural heart disease without symptoms, i.e. heart failure Stage B (HF‐B), may be as high as one in four women in the first year postpartum. We hypothesize that a significant number of formerly pre‐eclamptic women with HF‐B postpartum are still in their resolving period and will not have HF‐B during follow‐up. Methods: In this prospective longitudinal cohort study, we included 69 formerly pre‐eclamptic women who underwent serial echocardiographic measurements at 1 and 4 years postpartum. HF‐B was diagnosed as left ventricular hypertrophy (left ventricular mass index (LVMi) > 95 g/m 2 ), concentric remodeling (relative wall thickness > 0.42 and LVMi ≤ 95 g/m 2 ), mild systolic dysfunction (left ventricular ejection fraction > 40% and < 55%) or asymptomatic valvular disease. Women were subdivided and analyzed according to HF‐B outcome: no HF‐B at either visit; HF‐B at first visit only; HF‐B at second visit only; HF‐B at both visits. Results: The prevalence of HF‐B in formerly pre‐eclamptic women was 23% in the first year postpartum and 23% after 4 years. At the second visit, HF‐B had resolved in 62.5% of affected women but was newly developed in 19% of initially unaffected women. At the first visit, 56% of women diagnosed with HF‐B had reduced systolic function whereas at the second visit 69% of women with HF‐B had concentric remodeling with mostly normal ejection fraction, consistent with diastolic dysfunction. Conclusions: The prevalence of HF‐B can be considered consistently high (1 in 4) amongst formerly pre‐eclamptic women at follow‐up. Nonetheless, at an individual level, more than 60% of women found initially to be affected by HF‐B will recover, whilst about 20% of formerly pre‐eclamptic women with normal echocardiography in the first year postpartum will develop HF‐B over the following years. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.